Strategic Business Plan for Lantai Bumi Expansion to Jakarta: Achieving Sustainable Growth and Competitive Advantage in The Coffee Industry - Apriady, Dedy (Syntax Literate, 2025)
This study presents a strategic business plan for Lantai Bumi Coffee’s expansion into Jakarta, aiming to achieve sustainable growth and competitive advantage in the coffee industry. The research investigates the current coffee market dynamics in Indonesia, highlighting the increasing demand for specialty coffee and the proliferation of coffee shops. It identifies key challenges, including employee retention and fierce competition. Utilizing qualitative research methods, including focus group discussions and interviews, the study analyzes consumer preferences and operational strategies. The findings indicate that Lantai Bumi can differentiate itself through high-quality products, a unique café atmosphere, and effective marketing strategies. Financial projections suggest a promising return on investment, supported by a strong customer base and a favorable location in Kemang. This business plan outlines the necessary steps for successful entry into the Jakarta market, emphasizing the importance of innovation and community engagement.